India and politics and modern Nepal - Bhattacharjee, G. P. (Calcutta, 1970)
In preparing this book I have received valuable assistance from some of my Nepalese students who read International Relations in the Jadavpur University. In this connection the names of Puspa Raja Manandhar, Syed Anwar, Narayan Thapa and Sashi Malla should particularly be mentioned. Puspa Raja supplied me with a large number of journals and documents published in Nepal. He also helped me to go through a number of books, journals and documents written in Nepalese language. During my visit to Nepal in June 1969 I received effective co-operation from Pusparaja and Anwar as well as from Mr. Tirtha Lal Shrestha and Miss Indira Manandhar. Miss Indira Manandhar who works under the Ford Foundation in the Nepal Planning Commission helped me with valuable materials. I am also grateful to the officers of the Singha Darbar and the Indian Co-operation Mission in Kathmandu for assistance. I am also deeply indebted to many of the political leaders of modern Nepal whom I could meet either in India or in Nepal. Mr. D. K. Sahi, editor of the Nepal To-day, helped me much with his first-hand knowledge of the politics of modern Nepal. Lastly, I must mention the valuable assistance I received from my esteemed friend Shri Sushil Mukherjea who suggested important changes in the manuscript besides helping me in publishing the book. Without their assistance and co-operation it would have been difficult for me to write and publish this book. The views expressed in the book are however my own, and nobody else should be made respon sible for them.
Keywords: India - foreign relations - Nepal